Talking to healthcare providers about sex in later life: Findings from a qualitative study with older Australian men and women - Fileborn, B.; Lyons, A.; Heywood, W.; Hinchliff, S.; Malta, S.; Dow, B.; Brown, Graham; Barrett, C.; Minichiello, V. (Wiley-Blackwell Publishing Asia, 2017)
Â© 2017 AJA Inc. Objective: Healthcare providers (HCPs) can play an important role in supporting the sexual health of older adults; however, we know little about the experiences of older people in talking to HCPs about sex. This article examines older adults' experiences and perceptions of talking to HCPs about sex. Methods: Semi-structured interviews were conducted with 30 men and 23 women aged 60 and older recruited from a national, online survey of older Australians. Data were analysed using a thematic approach. Results: Most participants did not discuss sex with their HCP, and their HCP did not raise it. For those who did discuss sex with a HCP, negative and stigmatising responses were common. Positive responses could facilitate access to sexual health care. Conclusion: Older people benefit when HCPs are proactive and ask about sexual health. Education in how to talk about sex with older people would also be beneficial for HCPs.